A selective catalytic reduction N2O catalyst using waste vanadium-titanium denitration catalyst as raw material and preparation method thereof
By using the waste vanadium titanium denitrification catalyst as raw material, the high-energy (001) crystal surface exposed TiO2 is prepared by hydrothermal synthesis method, which solves the problem of low efficiency in catalytic removal of N2O, and achieves the effect of efficient removal of N2O at a lower temperature.
Patent Information
- Application Number
- CN202211518914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-11-30
AI Technical Summary
Existing N2O selective catalytic reduction catalysts are less efficient when catalyzing the removal of N2O, mainly because the bond energy of N2O is higher and the energy required to destroy the bond energy is higher.
By using the used vanadium titanium denitrification catalyst as raw material, potassium iodide is used as a high-energy crystal surface exposure agent, the crystal form and crystal surface exposure ratio of TiO2 are changed by hydrothermal synthesis method, and a rutile-type TiO2 exposed on the high-energy (001) crystal surface is prepared to enhance the catalytic activity of the catalyst.
It is achieved efficient removal of N2O at lower temperatures, and the N2O conversion efficiency of the catalyst is greater than 90% within 250-500°C. At the same time, the cost is reduced through the reuse of waste catalysts.
Smart Images

Figure CN116139891B_ABST
Abstract
Description
Technical Field
[0001] The invention provides a selective catalytic reduction N2O catalyst using waste vanadium titanium denitration catalyst as raw material and a preparation method thereof, belonging to the field of resource utilization of waste denitration catalyst, environmentally friendly catalytic materials and air pollution control. Background Art
[0002] Nitrous oxide (N2O), also known as laughing gas, is a colorless and sweet gas. It is also an important greenhouse gas. Compared with CO2, although the content of N2O is very low, its global warming potential is about 300 times higher than that of CO2. Its estimated lifespan in the atmosphere is about 130 years, which has a great effect on the global greenhouse effect. At the same time, it also has a great destructive effect on the ozone layer. At present, with the development of industrialization, N2O produced by anthropogenic sources has overwhelmed the ecosystem and caused increasingly serious consequences. Therefore, it is very important to develop effective methods for treating N2O in actual industrial production. At present, the more mature N2O treatment technologies include high-temperature decomposition, direct catalytic decomposition, and selective catalytic reduction (SCR) of N2O. The high-temperature decomposition method requires a temperature above 800°C, high energy consumption, low conversion efficiency, and secondary pollution, which is not suitable for large-scale application. The direct catalytic reduction method has high catalytic decomposition efficiency, but has high requirements for flue gas composition. It needs to be clean gas without other impurity gases and is not suitable for industrial flue gas. The selective catalytic reduction method has high catalytic efficiency and can effectively reduce the catalytic reduction temperature. Common reducing agents include NH3, CH4, CO, etc.
[0003] Patents at home and abroad have disclosed N2O catalysts and preparation methods. The patent (CN 104475112 B) discloses a catalyst for catalytic decomposition of N2O under high-temperature water-through oxygen conditions and its preparation method. The catalyst is composed of ZnAl2O4 as a carrier to load active components CuO and one or two active components of Fe, Co, Ni, Zr, Mg, Ca, and Ba oxides. The preparation method is as follows: (1) preparing a ZnAl2O4 carrier; (2) preparing a mixed solution of active components; (3) immersing the ZnAl2O4 carrier in the active component solution, heating and stirring until uniform dispersion, drying, and then stirring evenly with fillers and peptizing agents, kneading and extruding into strips, placing and drying, and then calcining in a muffle furnace at room temperature to obtain a catalyst for catalytic decomposition of N2O under high-temperature water-through oxygen conditions. The patent (CN103506129A) discloses a method for preparing a catalyst for directly catalytically decomposing N2O, which belongs to the technical field of environmental protection catalytic materials and air pollution control. The catalyst uses a composite material as a carrier, and is loaded with a double-layer metal oxide through two or more impregnations. The composite material is a molded product of two or more of clay, activated carbon, bakelite powder, sesbania powder, special pseudo-boehmite powder, SiO2, TiO2, ZrO2, sand or high-alumina cement. The first layer of metal oxide is a composite oxide of Cu, Zn, and Ni, and the second layer of metal oxide is an oxide of one element among Ba, Ca, Mg, Y, Cr, Mo, Co, La, Pr or Nd. The catalyst has a columnar, clover or pentagonal shape, and a size of 1-20 mm in outer diameter. The catalyst can be widely used in nitric acid plants, adipic acid plants and other industrial processes that produce N2O to eliminate and decompose N2O. However, current research on N2O decomposition catalysts is mostly focused on high-temperature decomposition and direct catalytic decomposition. The high-temperature decomposition method uses a relatively high temperature, higher than 1000°C, and the direct catalytic decomposition method is not suitable for complex flue gas conditions, so it is difficult to achieve industrialization. The selective catalytic reduction method has a low temperature and high catalytic efficiency, and has a good application prospect in removing N2O from industrial flue gas. Summary of the invention
[0004] The purpose of the present invention is to address the problems existing in the existing N2O selective catalytic reduction catalysts and to propose a selective catalytic reduction N2O catalyst using waste vanadium-titanium denitration catalyst as raw material. Another purpose of the present invention is to provide a method for preparing the above catalyst.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The technical solution of the present invention is as follows: the present invention uses waste vanadium titanium denitration catalyst as raw material and potassium iodide as high-energy crystal face exposing agent, and changes the TiO2 crystal form and crystal face exposure ratio in the waste vanadium titanium denitration catalyst by hydrothermal synthesis to prepare rutile TiO2 with high-energy (001) crystal face exposure. Conventional SCR denitration catalysts have relatively low efficiency in catalytic removal of N2O, mainly because the bond energy of N2O is higher than that of NO and NO2, and the energy required to destroy the bond energy is higher. The catalyst exposes the high-energy crystal face of TiO2 by hydrothermal synthesis, and can provide more energy to destroy the bond energy of N2O during the selective catalytic reduction process. The advantages of the catalyst are: (1) the catalyst raw material is widely available, and waste denitration catalyst is used as raw material, which can realize waste recycling on the one hand and reduce the catalyst cost on the other hand; (2) potassium iodide is used as a high-energy crystal face exposing agent, and the rutile TiO2 with high (001) crystal face exposure prepared by hydrothermal synthesis improves the catalytic activity of the catalyst. In addition, the co-catalyst Ce 3+ / Ce 4+ Reversible redox cycles are easily possible, giving cerium dioxide excellent redox properties and special Lewis acid-base active sites. These special active sites alleviate catalyst poisoning and extend the service life of the catalyst.
[0007] The specific technical scheme of the present invention is:
[0008] A catalyst for selective catalytic reduction of N2O, the catalyst comprising palladium oxide as a catalytically active component, cerium oxide and manganese oxide as co-catalysts, and potassium iodide as a high-energy crystal surface exposing agent;
[0009] The catalyst carrier is prepared by the following method:
[0010] The waste vanadium titanium denitration catalyst is crushed and sieved, potassium iodide and deionized water are added and stirred evenly, and then transferred to a hydrothermal reactor for hydrothermal activation. The mixture obtained after the hydrothermal activation is dried and then placed in a muffle furnace for roasting to obtain a catalyst carrier with high-energy crystal face 001 exposed;
[0011] Wherein, based on the waste vanadium titanium denitration catalyst, the mass percentage of the active component is 0.5% to 2%, the mass percentage of the promoter is 5% to 35%, and the mass percentage of the high-energy crystal surface exposing agent is 1% to 5%.
[0012] In the technical solution of the present invention: the waste vanadium titanium denitration catalyst uses TiO2 as a carrier, MoO3 and V2O5 as active components, and the rest are additives;
[0013] The TiO2 carrier is 70% to 85% of the content of the waste vanadium titanium denitration catalyst, and the active components MoO3 and V2O5 are 3% to 7% and 1% to 3% of the content of the waste vanadium titanium denitration catalyst respectively.
[0014] In the technical solution of the present invention, the mass ratio of cerium oxide to manganese oxide in the co-catalyst is 1:(0.2-0.4).
[0015] In the technical solution of the present invention: the high-energy crystal plane (001) is the main exposed crystal plane of TiO2, the main component of the waste vanadium-titanium denitrification catalyst, which is (001).
[0016] In the technical solution of the present invention: the sieving mesh number in the preparation method of the catalyst carrier is 80 to 100 meshes.
[0017] In the technical solution of the present invention: the mass ratio of the waste vanadium titanium denitration catalyst, potassium iodide and deionized water described in the preparation method of the catalyst carrier is 1: (0.01-0.05): (10-20).
[0018] In the technical scheme of the present invention: in the preparation method of the catalyst carrier, the hydrothermal temperature is 180-220° C., the hydrothermal time is 18-24 hours; the drying temperature is 60-80° C., the drying time is 4-6 hours; the roasting temperature is 500-600° C., and the roasting time is 2-4 hours.
[0019] A method for preparing the above-mentioned selective catalytic reduction of N2O catalyst, the steps of the method are as follows:
[0020] (1) Preparation of active component precursor solution
[0021] Adding palladium salt to deionized water and stirring evenly to obtain active component precursor solution A;
[0022] (2) Preparation of active component precursor solution
[0023] Adding cerium salt and manganese salt into deionized water and stirring evenly to obtain a co-catalyst precursor solution B;
[0024] (3) Catalyst preparation
[0025] The catalyst carrier and the active component precursor solution A and the co-catalyst precursor solution B obtained in step (1) and step (2) are stirred uniformly at 70-90° C., transferred to a forced air drying oven for drying, and then placed in a muffle furnace for secondary calcination in air atmosphere to obtain a catalyst.
[0026] In the above preparation method: the palladium salt is palladium chloride; the cerium salt in step (3) is cerium nitrate hexahydrate, and the manganese salt is manganese chloride tetrahydrate.
[0027] In the above preparation method: the drying temperature is 80-100°C, the drying time is 2-3h, the secondary roasting temperature is 500-700°C, and the secondary roasting time is 4-6h.
[0028] Application of the catalyst prepared above in selective catalytic reduction of N2O.
[0029] The catalytic reaction conditions and results of the present invention are as follows: 2 mL of catalyst is loaded into a catalyst performance evaluation reaction device, the inner diameter of the quartz tube in the evaluation reaction device is 10 mm, and the reaction gas is introduced for activity evaluation. The simulated gas composition is: N2O (200 ppm), NH3 (400 ppm), O2 (10%), N2 as carrier gas, the total gas flow rate is 400 mL / min, the catalytic reaction test temperature range is 200-500°C, and the test results show that the N2O removal efficiency is greater than 90% within 250-500°C.
[0030] Beneficial effects:
[0031] The selective catalytic reduction N2O catalyst prepared by the present invention using waste vanadium titanium denitration catalyst as raw material can not only realize the treatment and high value-added resource utilization of waste denitration catalyst, but also realize the efficient removal of N2O at a relatively low temperature. The catalyst of the present invention has low applicable temperature and high conversion efficiency. The N2O conversion efficiency is greater than 90% within 250-500°C, high selectivity, simple preparation process, low cost, and broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The activity diagram of the catalyst prepared in Examples 1 to 3;
[0033] Figure 2 The activity diagrams of the catalysts prepared in Comparative Examples 1 to 3;
[0034] Figure 3 A high-resolution transmission electron microscopy image of the catalyst support exposed to the high-energy crystal plane (001) prepared in Example 1;
[0035] Figure 4 A high-resolution transmission electron microscopy image of the catalyst support exposed to the high-energy crystal plane (001) prepared in Example 2;
[0036] Figure 5 This is the electron diffraction ring pattern of the catalyst support exposed to the high-energy crystal plane (001) prepared in Example 2. DETAILED DESCRIPTION
[0037] The waste vanadium titanium denitrification catalyst used in the embodiment has TiO2 as a carrier, and MoO3 and V2O5 as the main active components; wherein the TiO2 carrier is 85% of the content of the waste vanadium titanium denitrification catalyst, the main active components MoO3 and V2O5 are 5% and 3% of the content of the waste vanadium titanium denitrification catalyst respectively, and the content of other impurities is 7%, and no specific method is required for preparation.
[0038] The detection instrument used for the test results is the Laoying 3021 portable carbon emission monitor.
[0039] The present invention is further described below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto: Embodiment 1
[0040] (1) Preparation of catalyst carrier
[0041] Weigh 10g of waste vanadium titanium denitrification catalyst, add 0.1g potassium iodide and 100g deionized water, stir evenly and transfer to a 200mL polytetrafluoroethylene hydrothermal reactor, perform hydrothermal reaction at 180°C for 24h, take out and cool to room temperature, collect the mixture obtained after the reaction, place it in a blast drying oven at 60°C for 6h, then place it in a muffle furnace and calcine at 500°C for 4h to obtain a catalyst carrier with high-energy crystal plane (001) exposed; Figure 3 As shown, the carrier is a truncated octahedral structure. According to relevant literature, the main exposed crystal face of the truncated octahedral structure is (001);
[0042] (2) Preparation of active component precursor solution
[0043] Weigh 0.0631 g of palladium chloride, add 10 mL of deionized water and stir evenly to obtain active component precursor solution A;
[0044] (3) Preparation of active component precursor solution
[0045] Weigh 1.0513 g of cerium nitrate hexahydrate and 0.1896 g of manganese chloride tetrahydrate, add 10 mL of deionized water and stir evenly to obtain a co-catalyst precursor solution B;
[0046] (4) Catalyst preparation
[0047] Based on the carrier mass being 100%, the mass percentage of the active component in the carrier mass is 0.5%, and the mass percentage of the co-catalyst in the carrier mass is 5%. The active component precursor ion solution prepared in step (2) and the co-catalyst precursor ion solution prepared in step (3) are mixed, and added together to the catalyst carrier prepared in step (1), stirred at 80°C for 20 minutes, transferred to a forced air drying oven at 100°C for 2 hours, and then placed in a muffle furnace and calcined for a second time at 700°C in an air atmosphere for 4 hours to obtain a catalyst.
[0048] (5) Catalytic activity test
[0049] Take 2mL of catalyst sample and put it into the catalyst performance evaluation reaction device. The inner diameter of the quartz tube in the evaluation reaction device is 10mm. The simulated gas is introduced for activity evaluation. The simulated gas composition is: N2O (200ppm), NH3 (400ppm), O2 (10%), N2 as carrier gas, the total gas flow rate is 400mL / min, and the catalytic reaction test temperature range is 200-500℃. The test results show that the N2O removal efficiency in the temperature range of 250-500℃ for 2min is as low as 90.6% and as high as 99.1%.
[0050] Example 2
[0051] (1) Preparation of catalyst carrier
[0052] Weigh 10g of waste vanadium titanium denitrification catalyst, add 0.5g potassium iodide and 200g deionized water, stir evenly and transfer to a 250mL polytetrafluoroethylene hydrothermal reactor, perform hydrothermal reaction at 200℃ for 22h, take out and cool to room temperature, collect the mixture obtained after the reaction, place it in a blast drying oven at 70℃ for 5h, and then place it in a muffle furnace and calcine at 550℃ for 3h to obtain a catalyst carrier with high-energy crystal plane (001) exposed; Figure 4 and Figure 5 As shown, the carrier is a truncated octahedral structure. According to the analysis of the distance from the electron diffraction ring to the diffraction center and related literature, the main exposed crystal plane of the truncated octahedral structure is (001);
[0053] (2) Preparation of active component precursor solution
[0054] Weigh 0.2525 g of palladium chloride, add 10 mL of deionized water and stir evenly to obtain active component precursor solution A;
[0055] (3) Preparation of active component precursor solution
[0056] Weigh 7.3591 g of cerium nitrate hexahydrate and 1.3272 g of manganese chloride tetrahydrate, add 50 mL of deionized water and stir evenly to obtain a co-catalyst precursor solution B;
[0057] (4) Catalyst preparation
[0058] Based on the carrier mass being 100%, the mass percentage of the active component in the carrier mass is 2%, and the mass percentage of the co-catalyst in the carrier mass is 35%. The active component precursor ion solution prepared in step (2) and the co-catalyst precursor ion solution prepared in step (3) are mixed, and added together to the catalyst carrier prepared in step (1), stirred at 70°C for 20 minutes, transferred to a forced air drying oven at 60°C for 3 hours, and then placed in a muffle furnace with air as the atmosphere for secondary calcination at 500°C for 6 hours to obtain a catalyst.
[0059] (5) Catalytic activity test
[0060] Take 2mL of catalyst sample and put it into the catalyst performance evaluation reaction device. The inner diameter of the quartz tube in the evaluation reaction device is 10mm. The simulated gas is introduced for activity evaluation. The simulated gas composition is: N2O (200ppm), NH3 (400ppm), O2 (10%), N2 as carrier gas, the total gas flow rate is 400mL / min, and the catalytic reaction test temperature range is 200-500℃. The test results show that the N2O removal efficiency is as low as 92.3% in the temperature range of 250-500℃ for 2min.
[0061] Example 3
[0062] (1) Preparation of catalyst carrier
[0063] Weigh 10g of waste vanadium-titanium denitrification catalyst, add 0.3g of potassium iodide and 150g of deionized water, stir evenly and transfer to a 200mL polytetrafluoroethylene hydrothermal reactor. After hydrothermal reaction at 180°C for 24h, take out and cool to room temperature. Collect the precipitate obtained after the reaction and place it in a forced air drying oven at 60°C for 6h, then place it in a muffle furnace and calcine at 500°C for 4h to obtain a high-energy crystal face (001) exposed catalyst carrier.
[0064] (2) Preparation of active component precursor solution
[0065] Weigh 0.1578 g of palladium chloride, add 10 mL of deionized water and stir evenly to obtain active component precursor solution A;
[0066] (3) Preparation of active component precursor solution
[0067] Weigh 4.2052 g of cerium nitrate hexahydrate and 0.7584 g of manganese chloride tetrahydrate, add 15 mL of deionized water and stir evenly to obtain a co-catalyst precursor solution B;
[0068] (4) Catalyst preparation
[0069] Based on the carrier mass being 100%, the mass percentage of the active component in the carrier mass is 1.25%, and the mass percentage of the co-catalyst in the carrier mass is 20%. The active component precursor ion solution prepared in step (2) and the co-catalyst precursor ion solution prepared in step (3) are mixed, and added together to the catalyst carrier prepared in step (1), stirred at 75°C for 20 minutes, transferred to a forced air drying oven at 90°C for drying for 2.5 hours, and then placed in a muffle furnace with air as the atmosphere at 600°C for a second calcination for 5 hours to obtain a catalyst.
[0070] (5) Catalytic activity test
[0071] Take 2mL of catalyst sample and put it into the catalyst performance evaluation reaction device. The inner diameter of the quartz tube in the evaluation reaction device is 10mm. The simulated gas is introduced for activity evaluation. The simulated gas composition is: N2O (200ppm), NH3 (400ppm), O2 (10%), N2 as carrier gas, the total gas flow rate is 400mL / min, and the catalytic reaction test temperature range is 200-500℃. The test results show that the N2O removal efficiency is as low as 91% in the temperature range of 250-500℃ for 2min.
[0072] Comparative Example 1
[0073] (1) Preparation of catalyst
[0074] Except that potassium iodide is not added in step (1) during the catalyst preparation, other conditions are the same as those in Example 1;
[0075] (2) Catalyst activity test
[0076] Take 2mL of catalyst sample and put it into the catalyst performance evaluation reaction device. The inner diameter of the quartz tube in the evaluation reaction device is 10mm, and simulated gas is introduced for activity evaluation. The simulated gas composition is: N2O (200ppm), NH3 (400ppm), O2 (10%), N2 as carrier gas, the total gas flow rate is 400mL / min, and the catalytic reaction test temperature range is 200-500℃. The test results show that the highest N2O removal efficiency in the temperature range of 200-500℃ for 2min is 53.5%.
[0077] (3) Contrast effect
[0078] Compared with Example 1, potassium iodide is not added in step (1) during catalyst preparation, which fails to expose the high-energy crystal faces of TiO2, resulting in a decrease in activity and a low catalytic effect on N2O.
[0079] Comparative Example 2
[0080] (1) Preparation of catalyst
[0081] Except that cerium nitrate hexahydrate is not added in step (3) during the catalyst preparation, other conditions are the same as those in Example 1;
[0082] (2) Catalyst activity test
[0083] Take 2mL of catalyst sample and put it into the catalyst performance evaluation reaction device. The inner diameter of the quartz tube in the evaluation reaction device is 10mm. Pass the simulated gas to evaluate the activity. The simulated gas composition is: N2O
[0084] (200ppm), NH3 (400ppm), O2 (10%), and N2 were used as carrier gases. The total gas flow rate was 400mL / min, and the catalytic reaction test temperature range was 200-500℃. The test results showed that the N2O removal efficiency was as high as 63.9% in the temperature range of 250-500℃ for 2min.
[0085] (3) Contrast effect
[0086] Compared with Example 2, no cerium nitrate hexahydrate is added in step (1) during catalyst preparation. Although the catalyst forms exposed high-energy crystal faces, the co-catalyst is pure manganese oxide, not a manganese-cerium composite oxide. The redox performance of the catalyst is reduced, resulting in reduced catalyst activity.
[0087] Comparative Example 3
[0088] (1) Preparation of catalyst
[0089] Except that manganese chloride tetrahydrate is not added in step (3) during the catalyst preparation, other conditions are the same as those in Example 1;
[0090] (2) Catalyst activity test
[0091] Take 2mL of catalyst sample and put it into the catalyst performance evaluation reaction device. The inner diameter of the quartz tube in the evaluation reaction device is 10mm. The simulated gas is introduced for activity evaluation. The simulated gas composition is: N2O (200ppm), NH3 (400ppm), O2 (10%), N2 as carrier gas, the total gas flow rate is 400mL / min, and the catalytic reaction test temperature range is 200-500℃. The test results show that the highest N2O removal efficiency is 64.1% in the temperature range of 250-500℃ for 2min.
[0092] (3) Contrast effect
[0093] Compared with Example 3, manganese chloride tetrahydrate is not added in step (1) during catalyst preparation, and the co-catalyst is pure cerium oxide instead of manganese-cerium composite oxide, so the redox performance of the catalyst is reduced, thereby causing the catalyst activity to decrease.
Claims
1. A catalyst for selective catalytic reduction of N2O, characterized in that: The catalyst uses palladium oxide as a catalytic active component, cerium oxide and manganese oxide as co-catalysts, and waste vanadium titanium denitration catalyst as a raw material to prepare the catalyst carrier; The catalyst carrier is prepared by the following method: The waste vanadium titanium denitration catalyst is crushed and sieved, potassium iodide and deionized water are added and stirred evenly, and then transferred to a hydrothermal reactor for hydrothermal activation. The mixture obtained after the hydrothermal activation is dried and then placed in a muffle furnace for roasting to obtain a catalyst carrier with a high-energy crystal plane (001) exposed; wherein potassium iodide is a high-energy crystal plane exposing agent; Wherein, based on the waste vanadium titanium denitration catalyst, the mass percentage of the active component is 0.5% to 2%, the mass percentage of the promoter is 5% to 35%, and the mass percentage of the high-energy crystal surface exposing agent is 1% to 5%; The high-energy crystal plane (001) is the main exposed crystal plane (001) of TiO2, the main component of the waste vanadium-titanium denitrification catalyst.
2. The catalyst according to claim 1, characterized in that: The waste vanadium titanium denitrification catalyst uses TiO2 as carrier, MoO3 and V2O5 as active components, and the rest as additives; The TiO2 carrier is 70% to 85% of the content of the waste vanadium titanium denitration catalyst, and the active components MoO3 and V2O5 are 3% to 7% and 1% to 3% of the content of the waste vanadium titanium denitration catalyst respectively.
3. The catalyst according to claim 1, characterized in that: The mass ratio of cerium oxide to manganese oxide in the co-catalyst is 1:(0.2-0.4).
4. The catalyst according to claim 1, characterized in that: The sieving mesh number in the preparation method of the catalyst carrier is 80 to 100 meshes.
5. The catalyst according to claim 1, characterized in that: The mass ratio of the waste vanadium titanium denitration catalyst, potassium iodide and deionized water described in the preparation method of the catalyst carrier is 1: (0.01-0.05): (10-20).
6. The catalyst according to claim 1, characterized in that: In the preparation method of the catalyst carrier, the hydrothermal temperature is 180-220°C, the hydrothermal time is 18-24h; the drying temperature is 60-80°C, the drying time is 4-6h; the roasting temperature is 500-600°C, and the roasting time is 2-4h.
7. A method for preparing a selective catalytic reduction N2O catalyst according to claim 1, characterized in that: The steps of this method are as follows: (1) Preparation of active component precursor solution Adding palladium salt to deionized water and stirring evenly to obtain active component precursor solution A; (2) Preparation of co-catalyst precursor solution Adding cerium salt and manganese salt into deionized water and stirring evenly to obtain a co-catalyst precursor solution B; (3) Catalyst preparation The catalyst carrier and the active component precursor solution A and the co-catalyst precursor solution B obtained in step (1) and step (2) are stirred uniformly at 70-90° C., transferred to a forced air drying oven for drying, and then placed in a muffle furnace for secondary calcination in air atmosphere to obtain a catalyst.
8. The preparation method according to claim 7, characterized in that: The palladium salt is palladium chloride; the cerium salt in step (2) is cerium nitrate hexahydrate, and the manganese salt is manganese chloride tetrahydrate; The drying temperature in step (3) is 80-100° C., the drying time is 2-3 hours, the secondary roasting temperature is 500-700° C., and the secondary roasting time is 4-6 hours.
9. Use of the catalyst according to claim 1 in the selective catalytic reduction of N2O.
Citation Information
Patent Citations
Preparation method of direct N2O catalytic decomposition catalyst
CN103506129A
Catalytic decomposition of n under the condition of high temperature water flow and oxygen flow 2 o Catalyst and its preparation method
CN104475112B
Catalyst for low temperature SCR denitration in cement industry and preparation method thereof
CN106076358A
Multifunctional catalyst, and preparation method and application thereof
CN111167487A